Pengaruh Tuturan Afasia terhadap Leksikal pada Tuturan Penderita Afasia: Suatu Kajian Neuro-Fonologi - Mhd. Johan; Robby Satria; Yunisa Oktavia (Lingua Susastra, 2022)
This study aims to explain the lexical forms and how the speech processes are produced by the respondents. This study involved respondents who experienced speech disorders, especially respondents who experienced aphasia. Several things are of particular concern in this research, especially the fading process, then the replacement process. Usually this change process is the most dominant thing in this case study.The next process is the added process, where this process is often also found in speech, sometimes the meaning is lost or meaningless. This study uses references such as the opinion of Sastra, Johan, and many other supporting theories that complement the validity of this research. In the implementation of this research, the method of participatory observation was used in the process of collecting data and completed with baiting techniques to lure respondents to speak. For data analysis, the distribution method is used, in other words, it is called the distribution method which is equipped with several techniques such as deletion, expansion, and replace techniques. From the technique will produce three processes.